The plays of J.M. Barrie : Peter Pan, or, The boy who would not grow up - Barrie, J. M. (James Matthew), 1860-1937. (United States : Paramount Pictures, 1928)
Peter Pan, the boy who never grew up, charms Wendy and her brothers so that they fly with him to Never Never Land. On this island of dreams and magic, they struggle to rescue the Lost Boys from Captain Hook and his band of pirates, encountering along the way the fairy Tinkerbell, a man-eating crocodile, and a band of valiant Indians.
Photographed by James Howe ; settings by Edward Smith.
Betty Bronson, Ernest Torrence, Virginia Brown Faire, Anna May Wong, Cyril Chadwick, Esther Ralston, George Ali, Mary Brian, Philippe de Lacy, Jack Murphy.
AFI/Walt Disney Films Collection.
AFI/Walt Disney Films Collection.
Walt Disney Company Collection.
Keywords: English Drama; Feature films; Fiction films; Fantasy films